Making the Misreporting Policies Less Onerous in De Minimis Cases. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
The Managing Director's Medium-Term Strategy referred to complex misreporting procedures for even trivial forms of misreporting and called for streamlining. This paper presents a proposal to reduce the burden of the Fund's misreporting policies in cases involving de minimis deviations from program conditions. The proposal is to consider deviations from a performance criterion or other condition to be de minimis where they are so small as to be trivial with no impact on the assessment of program performance.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Fund Policy; Fund; PP; Publication Policy; Rwanda